High-strength composite salt grouting material

By using the hybrid technology of composite salt grout A and B, the existing acrylic grouting materials are insufficient in terms of mechanical properties and anti -osmotic properties, and the excellent performance of high -intensity composite salt grouting materials.

CN119349970APending Publication Date: 2025-01-24SICHUAN TONGSHEN WATERPROOF ENG CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411516728.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The existing acrylate grouting materials cannot meet the demanding application scenarios of high waterproof and anti-seepage functions, especially in terms of mechanical properties and anti-seepage properties.

Method used

A high-strength composite salt grouting material is used, which is composed of composite salt grouting material A and composite salt grouting material B mixed at a mass ratio of 1:1. Composite salt grouting materials A and B are respectively composed of an acrylate mixture and a curing agent A (three Ethanolamine) and curing agent B (ammonium persulfate) are mixed.

Benefits of technology

It has achieved excellent mechanical properties and anti-seepage properties of high-strength composite salt grouting materials. The compressive strength of the solid sand body can reach 473kPa, and the permeability coefficient can reach 5.7×10-8cm/s.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005106912740000041
    Figure BDA0005106912740000041
  • Figure BDA0005106912740000101
    Figure BDA0005106912740000101
Patent Text Reader

Abstract

The invention relates to the technical field of constructional engineering materials, and discloses a high-strength composite salt grouting material. The high-strength composite salt grouting material is prepared by mixing a composite salt grouting material A and a composite salt grouting material B according to the mass ratio of 1: 1, wherein the composite salt grouting material A is formed by mixing an acrylate mixture and a curing agent A according to the mass ratio of 20: (0.1-0.5); the composite salt grouting material B is formed by mixing an acrylate mixture and a curing agent B according to the mass ratio of 20: (0.1-0.5). According to the high-strength composite salt grouting material disclosed by the invention, the compressive strength of a sand consolidation body can reach 473 kPa, the permeability coefficient can reach 5.7 * 10 <-8 > cm / s, and the high-strength composite salt grouting material has excellent mechanical properties and anti-seepage performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building engineering materials, in particular to a high-strength composite salt grouting material. Background Art

[0002] Acrylate grouting material is a hydrophilic grouting material with acrylate as the main component. It can be polymerized into a solid with gel properties. During the construction process, the acrylate grouting material is injected into the gaps in concrete or rock and soil by applying a certain pressure. The acrylate grouting material can produce a bonding effect with the surrounding concrete and rock and soil, effectively filling the gaps in the concrete and rock and soil; at the same time, the acrylate grouting material will expand to a certain extent during the polymerization process, which can effectively isolate water, thereby achieving the effect of preventing seepage and plugging leakage.

[0003] With the continuous upgrading of some engineering requirements, especially those application scenarios that require high waterproof and anti-seepage functions, the existing acrylate grouting materials can no longer meet these stringent requirements. Therefore, the development of a high-strength composite salt grouting material with better mechanical properties and anti-seepage performance has become a technical problem that needs to be solved urgently by those skilled in the art. Summary of the invention

[0004] The purpose of the present invention is to provide a high-strength composite salt grouting material, which has excellent mechanical properties and anti-seepage properties.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] One of the technical solutions of the present invention:

[0007] A high-strength composite salt grouting material, which is prepared by mixing composite salt grouting material A and composite salt grouting material B in a mass ratio of 1:1;

[0008] Among them, the composite salt grouting material A is mixed with an acrylate mixture and a curing agent A in a mass ratio of 20: (0.1-0.5); the composite salt grouting material B is mixed with an acrylate mixture and a curing agent B in a mass ratio of 20: (0.1-0.5).

[0009] Furthermore, the curing agent A is triethanolamine.

[0010] Furthermore, the curing agent B is ammonium persulfate.

[0011] Furthermore, the acrylate mixture comprises the following raw materials in parts by weight:

[0012] 300-320 parts of water, 0.1-1 parts of hydroquinone, 170-190 parts of acrylic acid, 15-25 parts of methacrylic acid, 5-10 parts of butyl acrylate, 70-90 parts of magnesium oxide, 10-15 parts of N-hydroxyethyl acrylamide, 10-15 parts of diethylenetriamine, 2-5 parts of dispersant, 2-5 parts of defoaming agent, 140-160 parts of calcined kaolin, and 220-240 parts of heavy calcium carbonate.

[0013] Furthermore, the preparation method of the acrylate mixture comprises the following steps:

[0014] 1) adding hydroquinone, acrylic acid, methacrylic acid and butyl acrylate into water and stirring to obtain premix I;

[0015] 2) adding magnesium oxide to the premix I obtained in step 1) and stirring to obtain premix II;

[0016] 3) adding N-hydroxyethyl acrylamide and diethylenetriamine to the premix II obtained in step 2) and stirring to obtain premix III;

[0017] 4) adding the dispersant, defoamer, calcined kaolin and heavy calcium carbonate to the premix III obtained in step 3), stirring and filtering to obtain the acrylate mixture.

[0018] Furthermore, in step 1), the stirring is specifically: controlling the stirring speed to 40 r / min, and stirring for 5 to 10 minutes.

[0019] Furthermore, in step 2), the stirring is specifically as follows: controlling the temperature to 60° C., the stirring speed to 40 r / min, and stirring for 5 to 10 min.

[0020] Furthermore, in step 3), the stirring is specifically: controlling the stirring speed to 40 r / min, and stirring for 10 to 20 min.

[0021] Furthermore, in step 4), the stirring is specifically: controlling the stirring speed to 40 r / min, and stirring for 20 to 30 min.

[0022] The second technical solution of the present invention:

[0023] Application of the above high-strength composite salt grouting material in grouting.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] The high-strength composite salt grouting material disclosed in the present invention has a compressive strength of 473 kPa and a permeability coefficient of 5.7×10 -8 cm / s, with excellent mechanical properties and anti-seepage properties. DETAILED DESCRIPTION

[0026] Now, various exemplary embodiments of the present invention are described in detail, and this detailed description should not be considered as a limitation of the present invention, but should be understood as a more detailed description of certain aspects, characteristics and embodiments of the present invention. It should be understood that the terms described in the present invention are only for describing specific embodiments and are not used to limit the present invention.

[0027] In addition, for the numerical range in the present invention, it is understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0028] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0029] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.

[0030] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0031] In the following examples, all the raw materials used are commercially available, as shown in Table 1;

[0032] Table 1 Raw materials and specifications

[0033]

[0034] In the following embodiments, a method for preparing a high-strength composite salt grouting material comprises the following steps:

[0035] 1) Weigh each raw material according to the following mass parts:

[0036] 300-320 parts of water, 0.1-1 parts of hydroquinone, 170-190 parts of acrylic acid, 15-25 parts of methacrylic acid, 5-10 parts of butyl acrylate, 70-90 parts of magnesium oxide, 10-15 parts of N-hydroxyethyl acrylamide, 10-15 parts of diethylenetriamine, 2-5 parts of dispersant, 2-5 parts of defoamer, 140-160 parts of calcined kaolin, 220-240 parts of heavy calcium carbonate;

[0037] 2) adding the hydroquinone, acrylic acid, methacrylic acid and butyl acrylate weighed in step 1) into water, controlling the stirring speed to 40 r / min, stirring for 5 to 10 minutes, and obtaining premix I;

[0038] 3) adding the magnesium oxide weighed in step 1) to the premix I obtained in step 2), controlling the temperature to 60° C., stirring at a speed of 40 r / min, and stirring for 5 to 10 minutes to obtain premix II;

[0039] 4) adding the N-hydroxyethyl acrylamide and diethylenetriamine weighed in step 1) to the premix II obtained in step 3), controlling the stirring speed to 40 r / min, stirring for 10 to 20 minutes, and obtaining premix III;

[0040] 5) adding the dispersant, defoamer, calcined kaolin and heavy calcium carbonate weighed in step 1) to the premix III obtained in step 4), controlling the stirring speed to 40 r / min, stirring for 20 to 30 min, filtering to remove impurities, and obtaining an acrylate mixture;

[0041] 6) taking the acrylate mixture obtained in step 5), mixing the acrylate mixture with the curing agent A in a mass ratio of 20:(0.1-0.5), stirring for 10-30 minutes, and obtaining a composite salt grouting material A;

[0042] Wherein, curing agent A is triethanolamine;

[0043] 7) taking the acrylate mixture obtained in step 5), mixing the acrylate mixture with the curing agent B in a mass ratio of 20:(0.1-0.5), stirring for 10-30 minutes, and obtaining a composite salt grouting material B;

[0044] Wherein, curing agent B is ammonium persulfate;

[0045] 8) The composite salt grouting material A obtained in step 6) and the composite salt grouting material B obtained in step 7) are mixed in a mass ratio of 1:1, and stirred for 20 to 40 minutes to obtain the high-strength composite salt grouting material.

[0046] Example 1

[0047] A high-strength composite salt grouting material

[0048] 1) Weigh each raw material according to the following mass parts:

[0049] 300 parts of water, 0.1 parts of hydroquinone, 170 parts of acrylic acid, 15 parts of methacrylic acid, 5 parts of butyl acrylate, 70 parts of magnesium oxide, 10 parts of N-hydroxyethyl acrylamide, 10 parts of diethylenetriamine, 2 parts of dispersant, 2 parts of defoamer, 140 parts of calcined kaolin, 220 parts of heavy calcium carbonate;

[0050] 2) adding the hydroquinone, acrylic acid, methacrylic acid and butyl acrylate weighed in step 1) into water, controlling the stirring speed to 40 r / min, stirring for 5 minutes, and obtaining premix I;

[0051] 3) adding the magnesium oxide weighed in step 1) to the premix I obtained in step 2), controlling the temperature to 60° C., stirring at a speed of 40 r / min, and stirring for 5 min to obtain premix II;

[0052] 4) adding the N-hydroxyethyl acrylamide and diethylenetriamine weighed in step 1) to the premix II obtained in step 3), controlling the stirring speed to 40 r / min, stirring for 10 min, to obtain premix III;

[0053] 5) adding the dispersant, defoamer, calcined kaolin and heavy calcium carbonate weighed in step 1) to the premix III obtained in step 4), controlling the stirring speed to 40 r / min, stirring for 20 min, filtering to remove impurities, and obtaining an acrylate mixture;

[0054] 6) taking the acrylate mixture obtained in step 5), mixing the acrylate mixture with the curing agent A at a mass ratio of 20:0.1, and stirring for 10 minutes to obtain a composite salt grouting material A;

[0055] Wherein, curing agent A is triethanolamine;

[0056] 7) taking the acrylate mixture obtained in step 5), mixing the acrylate mixture with the curing agent B in a mass ratio of 20:0.1, stirring for 10 minutes, and obtaining a composite salt grouting material B;

[0057] Wherein, curing agent B is ammonium persulfate;

[0058] 8) The composite salt grouting material A obtained in step 6) and the composite salt grouting material B obtained in step 7) are mixed in a mass ratio of 1:1, and stirred for 20 minutes to obtain the high-strength composite salt grouting material.

[0059] Example 2

[0060] A high-strength composite salt grouting material

[0061] 1) Weigh each raw material according to the following mass parts:

[0062] 310 parts of water, 0.5 parts of hydroquinone, 180 parts of acrylic acid, 20 parts of methacrylic acid, 7 parts of butyl acrylate, 80 parts of magnesium oxide, 13 parts of N-hydroxyethyl acrylamide, 13 parts of diethylenetriamine, 3 parts of dispersant, 3 parts of defoamer, 150 parts of calcined kaolin, 230 parts of heavy calcium carbonate;

[0063] 2) adding the hydroquinone, acrylic acid, methacrylic acid and butyl acrylate weighed in step 1) into water, controlling the stirring speed to 40 r / min, stirring for 8 minutes, and obtaining premix I;

[0064] 3) adding the magnesium oxide weighed in step 1) to the premix I obtained in step 2), controlling the temperature to 60° C., stirring at a speed of 40 r / min, and stirring for 8 min to obtain premix II;

[0065] 4) adding the N-hydroxyethyl acrylamide and diethylenetriamine weighed in step 1) to the premix II obtained in step 3), controlling the stirring speed to 40 r / min, stirring for 15 min, to obtain premix III;

[0066] 5) adding the dispersant, defoamer, calcined kaolin and heavy calcium carbonate weighed in step 1) to the premix III obtained in step 4), controlling the stirring speed to 40 r / min, stirring for 25 min, filtering to remove impurities, and obtaining an acrylate mixture;

[0067] 6) taking the acrylate mixture obtained in step 5), mixing the acrylate mixture with the curing agent A at a mass ratio of 20:0.3, and stirring for 20 minutes to obtain a composite salt grouting material A;

[0068] Wherein, curing agent A is triethanolamine;

[0069] 7) taking the acrylate mixture obtained in step 5), mixing the acrylate mixture with the curing agent B in a mass ratio of 20:0.3, stirring for 20 minutes, and obtaining a composite salt grouting material B;

[0070] Wherein, curing agent B is ammonium persulfate;

[0071] 8) The composite salt grouting material A obtained in step 6) and the composite salt grouting material B obtained in step 7) are mixed in a mass ratio of 1:1, and stirred for 30 minutes to obtain the high-strength composite salt grouting material.

[0072] Example 3

[0073] A high-strength composite salt grouting material

[0074] 1) Weigh each raw material according to the following mass parts:

[0075] 320 parts of water, 1 part of hydroquinone, 190 parts of acrylic acid, 25 parts of methacrylic acid, 10 parts of butyl acrylate, 90 parts of magnesium oxide, 15 parts of N-hydroxyethyl acrylamide, 15 parts of diethylenetriamine, 5 parts of dispersant, 5 parts of defoamer, 160 parts of calcined kaolin, 240 parts of heavy calcium carbonate;

[0076] 2) adding the hydroquinone, acrylic acid, methacrylic acid and butyl acrylate weighed in step 1) into water, controlling the stirring speed to 40 r / min, stirring for 10 min, and obtaining premix I;

[0077] 3) adding the magnesium oxide weighed in step 1) to the premix I obtained in step 2), controlling the temperature to 60° C., stirring at a speed of 40 r / min, and stirring for 10 min to obtain premix II;

[0078] 4) adding the N-hydroxyethyl acrylamide and diethylenetriamine weighed in step 1) to the premix II obtained in step 3), controlling the stirring speed to 40 r / min, stirring for 20 min, to obtain premix III;

[0079] 5) adding the dispersant, defoamer, calcined kaolin and heavy calcium carbonate weighed in step 1) to the premix III obtained in step 4), controlling the stirring speed to 40 r / min, stirring for 30 min, filtering to remove impurities, and obtaining an acrylate mixture;

[0080] 6) taking the acrylate mixture obtained in step 5), mixing the acrylate mixture with the curing agent A at a mass ratio of 20:0.5, and stirring for 30 minutes to obtain a composite salt grouting material A;

[0081] Wherein, curing agent A is triethanolamine;

[0082] 7) taking the acrylate mixture obtained in step 5), mixing the acrylate mixture with the curing agent B in a mass ratio of 20:0.5, and stirring for 30 minutes to obtain a composite salt grouting material B;

[0083] Wherein, curing agent B is ammonium persulfate;

[0084] 8) The composite salt grouting material A obtained in step 6) and the composite salt grouting material B obtained in step 7) are mixed in a mass ratio of 1:1, and stirred for 40 minutes to obtain the high-strength composite salt grouting material.

[0085] Comparative Example 1

[0086] A composite salt grouting material

[0087] 1) Weigh each raw material according to the following mass parts:

[0088] 320 parts of water, 1 part of hydroquinone, 190 parts of acrylic acid, 25 parts of methacrylic acid, 10 parts of butyl acrylate, 90 parts of magnesium oxide, 15 parts of N-hydroxyethyl acrylamide, 15 parts of diethylenetriamine, 5 parts of dispersant, 5 parts of defoamer, 160 parts of calcined kaolin, 240 parts of heavy calcium carbonate;

[0089] 2) adding the hydroquinone, acrylic acid, methacrylic acid and butyl acrylate weighed in step 1) into water, controlling the stirring speed to 40 r / min, stirring for 10 min, and obtaining premix I;

[0090] 3) adding the magnesium oxide weighed in step 1) to the premix I obtained in step 2), controlling the temperature to 60° C., stirring at a speed of 40 r / min, and stirring for 10 min to obtain premix II;

[0091] 4) adding the N-hydroxyethyl acrylamide and diethylenetriamine weighed in step 1) to the premix II obtained in step 3), controlling the stirring speed to 40 r / min, stirring for 20 min, to obtain premix III;

[0092] 5) adding the dispersant, defoamer, calcined kaolin and heavy calcium carbonate weighed in step 1) to the premix III obtained in step 4), controlling the stirring speed to 40 r / min, stirring for 30 min, filtering to remove impurities, and obtaining an acrylate mixture;

[0093] 6) taking the acrylate mixture obtained in step 5), mixing the acrylate mixture with the curing agent at a mass ratio of 20:0.5, and stirring for 30 minutes to obtain the composite salt grouting material;

[0094] Wherein, the curing agent is triethanolamine.

[0095] Comparative Example 2

[0096] A composite salt grouting material

[0097] 1) Weigh each raw material according to the following mass parts:

[0098] 320 parts of water, 1 part of hydroquinone, 190 parts of acrylic acid, 25 parts of methacrylic acid, 10 parts of butyl acrylate, 90 parts of magnesium oxide, 15 parts of N-hydroxyethyl acrylamide, 15 parts of diethylenetriamine, 5 parts of dispersant, 5 parts of defoamer, 160 parts of calcined kaolin, 240 parts of heavy calcium carbonate;

[0099] 2) adding the hydroquinone, acrylic acid, methacrylic acid and butyl acrylate weighed in step 1) into water, controlling the stirring speed to 40 r / min, stirring for 10 min, and obtaining premix I;

[0100] 3) adding the magnesium oxide weighed in step 1) to the premix I obtained in step 2), controlling the temperature to 60° C., stirring at a speed of 40 r / min, and stirring for 10 min to obtain premix II;

[0101] 4) adding the N-hydroxyethyl acrylamide and diethylenetriamine weighed in step 1) to the premix II obtained in step 3), controlling the stirring speed to 40 r / min, stirring for 20 min, to obtain premix III;

[0102] 5) adding the dispersant, defoamer, calcined kaolin and heavy calcium carbonate weighed in step 1) to the premix III obtained in step 4), controlling the stirring speed to 40 r / min, stirring for 30 min, filtering to remove impurities, and obtaining an acrylate mixture;

[0103] 6) taking the acrylate mixture obtained in step 5), mixing the acrylate mixture with the curing agent at a mass ratio of 20:0.5, and stirring for 30 minutes to obtain the composite salt grouting material;

[0104] Wherein, the curing agent is ammonium persulfate.

[0105] Comparative Example 3

[0106] A composite salt grouting material

[0107] 1) Weigh each raw material according to the following mass parts:

[0108] 320 parts of water, 1 part of hydroquinone, 190 parts of acrylic acid, 25 parts of methacrylic acid, 10 parts of butyl acrylate, 90 parts of magnesium oxide, 15 parts of N-hydroxyethyl acrylamide, 15 parts of diethylenetriamine, 5 parts of dispersant, 5 parts of defoamer, 160 parts of calcined kaolin, 240 parts of heavy calcium carbonate;

[0109] 2) adding the hydroquinone, acrylic acid, methacrylic acid and butyl acrylate weighed in step 1) into water, controlling the stirring speed to 40 r / min, stirring for 10 min, and obtaining premix I;

[0110] 3) adding the magnesium oxide weighed in step 1) to the premix I obtained in step 2), controlling the temperature to 60° C., stirring at a speed of 40 r / min, and stirring for 10 min to obtain premix II;

[0111] 4) adding the N-hydroxyethyl acrylamide and diethylenetriamine weighed in step 1) to the premix II obtained in step 3), controlling the stirring speed to 40 r / min, stirring for 20 min, to obtain premix III;

[0112] 5) adding the dispersant, defoamer, calcined kaolin and heavy calcium carbonate weighed in step 1) to the premix III obtained in step 4), controlling the stirring speed to 40 r / min, stirring for 30 min, filtering to remove impurities, and obtaining an acrylate mixture;

[0113] 6) mixing curing agent A and curing agent B in a mass ratio of curing agent A to curing agent B of 1:11 to obtain a mixed curing agent;

[0114] Among them, curing agent A is triethanolamine, and curing agent B is ammonium persulfate

[0115] 7) Take the acrylate mixture obtained in step 5), and mix the acrylate mixture with the mixed curing agent obtained in step 6) at a mass ratio of 20:0.5, and stir for 30 minutes to obtain the composite salt grouting material.

[0116] The performance of the composite salt grouting materials prepared in Examples 1 to 3 was tested with reference to JC / T 2037-2010 "Compound Salt Grouting Materials". The performance test results are shown in Table 2.

[0117] Table 2 Performance test results

[0118]

[0119] From the data in Table 2, it can be seen that the high-strength composite salt grouting material prepared by the present invention has a compressive strength of 473 kPa and a permeability coefficient of 5.7×10 -8 cm / s, having excellent mechanical properties and anti-seepage properties; moreover, compared with Comparative Examples 1 to 2 in which only one curing agent is added and Comparative Example 3 in which different curing agents are first mixed and then the acrylate mixture is added, the mechanical properties and anti-seepage properties of the composite salt grouting materials prepared in Examples 1 to 3 are significantly improved.

[0120] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the specific implementation methods of the present invention can still be modified or replaced by equivalents. Any modification or equivalent replacement that does not depart from the spirit and scope of the present invention should be covered within the scope of protection of the claims of the present invention.

Claims

1. A high-strength composite salt grouting material, characterized in that: The high-strength composite salt grouting material is prepared by mixing composite salt grouting material A and composite salt grouting material B in a mass ratio of 1:1; Among them, the composite salt grouting material A is mixed with an acrylate mixture and a curing agent A in a mass ratio of 20: (0.1-0.5); the composite salt grouting material B is mixed with an acrylate mixture and a curing agent B in a mass ratio of 20: (0.1-0.5).

2. A high-strength composite salt grouting material according to claim 1, characterized in that: The curing agent A is triethanolamine.

3. A high-strength composite salt grouting material according to claim 1, characterized in that: The curing agent B is ammonium persulfate.

4. A high-strength composite salt grouting material according to claim 1, characterized in that: The acrylate mixture comprises the following raw materials in parts by weight: 300-320 parts of water, 0.1-1 parts of hydroquinone, 170-190 parts of acrylic acid, 15-25 parts of methacrylic acid, 5-10 parts of butyl acrylate, 70-90 parts of magnesium oxide, 10-15 parts of N-hydroxyethyl acrylamide, 10-15 parts of diethylenetriamine, 2-5 parts of dispersant, 2-5 parts of defoaming agent, 140-160 parts of calcined kaolin, and 220-240 parts of heavy calcium carbonate.

5. The high-strength composite salt grouting material according to claim 1, characterized in that: The preparation method of the acrylate mixture comprises the following steps: 1) adding hydroquinone, acrylic acid, methacrylic acid and butyl acrylate into water and stirring to obtain premix I; 2) adding magnesium oxide to the premix I obtained in step 1) and stirring to obtain premix II; 3) adding N-hydroxyethyl acrylamide and diethylenetriamine to the premix II obtained in step 2) and stirring to obtain premix III; 4) adding the dispersant, defoamer, calcined kaolin and heavy calcium carbonate to the premix III obtained in step 3), stirring and filtering to obtain the acrylate mixture.

6. A high-strength composite salt grouting material according to claim 5, characterized in that: In step 1), the stirring is specifically: controlling the stirring speed to 40 r / min and stirring for 5 to 10 minutes.

7. The high-strength composite salt grouting material according to claim 5, characterized in that: In step 2), the stirring is specifically as follows: controlling the temperature to 60° C., the stirring speed to 40 r / min, and stirring for 5 to 10 min.

8. The high-strength composite salt grouting material according to claim 5, characterized in that: In step 3), the stirring is specifically: controlling the stirring speed to 40 r / min and stirring for 10 to 20 min.

9. The high-strength composite salt grouting material according to claim 5, characterized in that: In step 4), the stirring is specifically as follows: controlling the stirring speed to 40 r / min and stirring for 20 to 30 min.

10. Use of the high-strength composite salt grouting material according to any one of claims 1 to 9 in grouting.